Descompunere în factori:
1. x^2+14x+49-5(x+7)
2. (x+2)(2x-1)^2-4x-8
Răspunsuri la întrebare
Răspuns de
4
x^2+14x+49-5(x+7) = x²+14x+49-5x-35 = x²+9x+14
(x+2)(2x-1)^2-4x-8 = (x+2)(4x²-4x+1)-4x-8 = 4x³-4x²+8x²-8x+2-4x-8 =
= 4x³+4x²-11x-6
(x+2)(2x-1)^2-4x-8 = (x+2)(4x²-4x+1)-4x-8 = 4x³-4x²+8x²-8x+2-4x-8 =
= 4x³+4x²-11x-6
Andrada0804:
Mersi
Răspuns de
1
a). (x+7)^2-5(x+7)=(x+7)(x+7-5)= (x+7)(x+2).
b).(x+2)(2x-1)^2-4(x+2)=(x+2)(2x-1)^2-4=(x+2)(4x^2-2x+1)-4
b).(x+2)(2x-1)^2-4(x+2)=(x+2)(2x-1)^2-4=(x+2)(4x^2-2x+1)-4
Alte întrebări interesante
Biologie,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă